Türkiye'nin dış ticaret politikaları - Kılıç, Alaattin (Fen Bilimleri Enstitüsü, 1992)
Bu çalışmada kuruluşundan günümüze kadar Türkiye Cumhuriyeti 'nin uygulamış olduğu Dış Ticaret Politikaları ve bu politikaların dış ticareti nasıl etkilediği açıklanmaya çalışılmıştır. Çalışma 5 bölümden oluşmakta dır. Giriş bölümünde dış ticaretin iktisadi kalkınmadaki önemi ele alınmıştır. İkinci bölümde dış ticaret politikaları hakkında bilgiler verilmiş, dış ticaret politikalarının amaçları, araçları ve ihracatı teşvik politikaları anlatılmıştır. Üçüncü bölümde dönemler itibariyle Türkiye'de uygulanan dış ticaret politikaları ve bunların sonuçları ele alınırken, dördüncü bölümde Türkiye'nin dış ticaretinin yapısı ve Türkiye dış ticaretinde önemli olan ülkeler ve bu ülkelerle yapılan dış ticaret anlatılmıştır. Beşinci ve son bölüm sonuç ve öneriler bölümüdür.

As an open market for the western countries, The Ottoman Empire was exploited by them for Long years. Turkey, as the winner of the war of independanae was surrounded by an opposing and hostile international setting. When the Turkish Republic was declared in 1923, the country has ah undeveloped social structure, and at the same time devastated by continuing wars. The low per capita income in the early years of the republic, reveals the poverty of the nation. Although we do not possess reliable figures for early 1925, the rough estimates for 1927 Suggest that the share of agriculture in the Gross National Product (GNP) was approximately 67 percent. Agrioulturel sector reflected the primitive social and eoonoraia conditions of the aountry. Although agricultural lands were partly owned by big land owners, the small peasant-farmers owned a great proportion of arable land. Both big land owners and small farmers were impoverished under a heavy tax burden; the high rents paid by some farmers depressed their position further. There was not any group in a position to accumulate capital and modernize agriculture. Big and medium sized industry had not been set-up in Turkey; so the import of industrial goods had to be paid partly by export of agrioulturel products, partly by foreign borrowing. As almost all industrial commodities were imported from western countries, the establishment of a national industry was against the interests of foreign countries as well as their representatives in business and in public administration in Turkey. Although some foreign aapital was invested in Turkey by concessionary companies, they were mainly interested in areas that were riskless and highly profitable in the short run. Foreign capital was invested in such areas as banking, mart ime transport, railways, mining and services. According to the first census made in 1927, the' population amounted to 13.6 million citizens, of which a great proportion were peasant-farmers, some 75 percent of the whale population. The Treaty of Lausanne, signed in 1924 between the new Turkish Republic and the western powers, brought to a olose the hostilities between Turkey and Greece. It had several far-reaching economic consequences for Turkey three of them were especially important. One of them is the payment of old Ottoman Debts. The second is the Abolition of Capitulations, and the third one is Custom Duties. The first important step was the Law of Encouragement of industry, passed in 1927. According to this law industrial activities was classified and contained several incentives for the establishment and operation of industrial concerns. Among them wereland procurement for private industrial firms, and preferential purchase of some commodities for official use. The efforts of the government produced their consequences in the late 1920 's; industrial production began to increase. The increase in the fields of sugar refining, cotton and woolen textiles, cement and coal was noteworthy. The most important event in this period was the preparation and initiation of the first-five year plan between 1931-1934. But this plan was quite different from todays economic development plans. The plan was suocesfully carried out by government to found and to operate some factories in branches such as chemistry, ceramics, iron, pulp, textile, etc. A second five-year plan, covering the 1938-1941 period, was prepared in 1937. But the projects of this plan were not complated because of the second world war. The first action of the Republic in the monetary field was the taking over of the paper money issued by the Ottoman empire in 1915. The old money was changed by a new issue in 1927-1928. The Lausanne Treaty did not permit the Republic to increase custom duties before 1929. This fact encouraged importers to profit from low rates, and the trade balance -x« » showed an unprecedented deficit in 1929 (while the Turkey import was 256,3 million Lira in 1929, it was 147,6 million Lira in 1930). Meanwhile, the activities of speculators were pushing the exchangerates up further. In 1929-1930 two laws were issued aiming to control foreign exchange markets, the first being the law refulating stock and foreign exchanges and the second being the law for the protection of Turkish currency. These laws limited transactions on foreign exchange markets to a considerable extend. Importers could buy foreign exchange only if they were allowed to by the government. Exporters had to sell their foreign currency revenue at a fixed rate to the government. In 1930 the Central Bank of Turkey was established, it was charged with conventional central banking functions. Although Turkey did not participate in the second world war, it was adversely affected by it. National income, which had begun to increase during the prewar years, decreased by some 20 percent during this period; the reason being the mobilization of a large army in preperation for war. During teh war, imports were greatly reduced due to the difficulty of procuring import commodities and difficulties in transporting them. At the same time, the demand for exports increased and the trade balance showed a surplus (from 1930 to 1946, except for 1938). In 1946 the currency was devalued and the new dollar rate was fixed at 1 dollar» 280 kuruş, which remained the same until 1958. After an increase between 1950-1953, exports began to decline steadily and pronouncedly when every economic! index was increasing. The decline continued until 1958. The decrease in exports could not be definitely explanied solely by various distortions created by inflation. With the emergence of payments difficulties in 1953 the government had to change the liberal import policy and to impose import controls. In adition to strict import licencing, subsidies ranging between 25 and 40 percent were being paid on certain exports, and aditional taxes were being imposed on certain imports, at rates ranging between 25 and 75 percent. The situation was very bad and -xi- even the most neocassary materials could not be imported. In faot, all imports practically stopped at the begining of 1958. So, in August 1958 the government ofielded and devalued the Turkish Lira. The import rate was raised to 1 dollar=902 kuruş. The import regime was changed. According to the new import regime, import commodities were classified under four categories. The problem between 1960-1970 was the permanent trade balance deficits. Exports increased by 83 per cent while imports increased by 100 per cent. Although there is not much difference in the rate of increase between imports and exports, as there was a large initial difference between imports and exports at the begining of the period, the balance of trade deficits amounted to a large sum. In I960, FOB import, while 422 millions of dollar, it was 849 millions of dollar in 1970, and FOB export while 336 millions of dollar in 1960, it was 586 millions of dollar in 1970, and the trade deficit was 381 millions of dollar in 1970. The trade deficit reached a towering heigh between 1970-1980. In this period exports increased by 4.95 fold while imports increased by 8.35 fold. The increase of imports in 1974 was spectacular. It is evident that the petroleum crisiss and the world price increases which followed heigh petroleum prices were the main factors causing such a great increase. The price increases of Turkish exports were very low and terms of trade worsened sensibly. In 1980-190 period exports increased by 4.45 fold while imports increased by 2,82 fold. Although the increases of export was higher than the increases of import, the trade deficit reached a towering heigh becoming 9,344 millions of dollar between 1970-1980 the increases of imports were much higher than the increases of exports. Some characteristics of Turkish exports can be classified like; 1. A great proportion of exports consisted o fagricultural exports, but the share of industrial goods has increased after 1980. ' 2. The increase in exports is lower than the increase in national income until 1980. But they became -Xll- higher than the increase in national income after 1980. 3. The degree of diversification of export commodities is well compared with many developing countries. Some characteristics of Turkish imports can be classified like; 1. Turkey imports commodities from many comuntries, but especially OECD countries are very important in Turkish total imports. 2. A great proportion of imports consists of raw materials and investment goods. Consumption goods are not so important in Turkey imports.
Turkish foreign trade policies
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Ekonomi; Dış ticaret politikaları; Ticaret; Türkiye; Economics; Foreign trade policies; Trade; Turkey